Pedagogical Objectives and Foundational Principles in Figurative Art Education - Bhattacharjee, Shilpi (Journal of Social Science and Humanities, 2025)
The subject of visual art, whether at the middle school or higher level, includes a wide range of materials and activities that help students develop their artistic skills and understand the essence of visual art. The figurative arts curriculum includes a wide range of topics, activities, and concepts that help students develop their skills in painting, drawing, and sculpture, using the human figure as a central element. The methodology of figurative culture as a science has the primary task of enabling the theoretical aspect of the knowledge achieved and systematized in the field of figurative art, so that future figurative teachers develop the skills of observation and introspection in the educational process, enabling critical assessment of methodological implementation and its advancement. Advancement comes only if we continuously verify the practices and experience of others, having a critical view of evaluation in relation to contemporary research in different fields, but which are specifically related to the art and methodology of figurative art. This implies joint research work of theorists and practitioners, scientists and artists and necessarily teachers. to achieve the most qualitative learning at all levels. The subject of Arts Methodology has the main aim - the objective - to enable future teachers - Teachers to professionally and independently develop the teaching process of figurative art competently and under the guidance of scientific literature and to permanently improve. The methodology of arts basically enables and directs - the artistic creativity of future pedagogues, the development of creative values of all school levels in figurative education. In addition to knowing the language of art, the application of figurative techniques and the knowledge of the values of the national and world cultural - artistic treasure, the future teachers will learn the elements of the educational - teaching methodology. They will also learn about the developmental processes of students' figurative creativity, selecting work methods and at the same time respecting the principles of figurative art, as well as preserving the individuality and accessibility of each student.